How functional foods endure throughout the shelf storage? Effects of packing materials and formulation on the quality parameters and bioactivity of smoothies. (January 2016) - Nunes, M. Antónia; Costa, Anabela S.G.; Barreira, João C.M.; Vinha, Ana F.; Alves, Rita C.; Rocha, Ada; Oliveira, M. Beatriz P.P.
Abstract: Smoothies are blended beverages that could contain fruit pulp, fruit juice, vegetables, yoghurt, milk, or honey. These beverages are typical examples of the food industry reply to the increase awareness of consumers for healthier foods with simple ingredients and clean labels. As emerging products, different profiling studies are needed to ensure their claimed properties. Accordingly, different physicochemical parameters, bioactive compounds, as well as the antioxidant activity, were assessed in commercial smoothies along different shelf storage periods. ANOVA, HCA and LDA statistical tools were used to allow a suitable comprehension of the obtained results. Some significant differences were found at initial time, which might be associated to smoothies' composition. On the other hand, the physicochemical and chromatic parameters were stable during the shelf storage, while the content in bioactive compounds and the antioxidant activity indicators were significantly affected (independently of the applied thermal treatment). Nevertheless, none of the assayed formulations or packing types showed to be more susceptible to undergone specifically relevant changes during shelf storage. Overall, the results advice in favor of an earlier consumption of these products (far from the expiring date) in order to obtain the desired health effects. Highlights: Different smoothies' formulations and packing types were assayed along shelf storage. Physicochemical parameters did not show overall trends for the assayed periods. Bioactive compounds and antioxidant activity decreased with shelf storage. Formulation and packing type did not seem to correlate with the detected differences. The results advice in favor of consuming smoothies at the earlier shelf-life stages.